Prevalence of odontogenic cysts in a group of Libyan population: A retrospective study - Buaoud MM; Musrati Ahmed; Hagström Jaana (India, 2025)
Background: Odontogenic cysts (OCs) are commonly encountered lesions affecting the human jaws having special clinical and radiographic features depending on cyst type. The aim of this study was to determine the prevalence of odontogenic jaw cysts in a Libyan population in Benghazi and to compare these data with previously published reports from Libyan and other geographic areas.
Materials and methods: This is a descriptive study where screening of 2189 biopsies (retrieved from the archives of The Department of Oral Pathology/University of Benghazi, Libya) was performed for the sake of recognizing the three cysts chosen for the purpose of this study.
Results: : Out of the screened lesions, 276 cases (12.6%) were diagnosed as odontogenic cysts in the period from 2006 to 2019. Of those, 67.39% were inflammatory and 32.61% were developmental in nature. Radicular cysts (60.5%) were the most frequent cysts followed by dentigerous cysts (14.8%) and keratocysts (14.5%). The mean ages of the patients were 32.3, 29.7, and 33.2 years, respectively. Occurrence of the cysts was noticed more in the maxilla than in the mandible (1.3:1). The overall male-to-female ratio was 1.1:1.
Conclusions: The prevalence of odontogenic cysts was similar to that reported in a previous study in Libya and other countries irrespective to WHO (2017) classification of odontogenic cysts.